Risk of Urinary Bladder Cancer in Patients With Inflammatory Bowel Diseases: A Meta-Analysis - Geng, Zhihua; Geng, Qing (Frontiers in Surgery, 2021)
In order to confirm the risk of urinary bladder cancer (BC) in inflammatory bowel diseases (IBD) patients, a systematic search of literature in PubMed, Cochrane, Embase and Web of Science databases was conducted. We identified 168 articles, of which 11 were eligible for analysis according to the inclusion and exclusion criteria. Our analysis included 165176 patients with IBD, with 491 of them having BC. Overall, the pooled standardized incidence ratios (SIRs) was 0.99 (95% CI:0.87-1.12; I2=0%;). Further subgroup analysis showed that the BC risk was higher in patients with Crohn’s disease (CD) (SIR:1.19; 95%CI: 0.94-1.44; I2=0%), but not in patients with ulcerative colitis (UC) (SIR: 0.92; 95% CI: 0.77-1.06; I2=0%). In the analysis of 2 case-control studies providing data on BC in UC and CD combined, IBD patients seemed to have a higher risk of BC than IBD-free patients (relative risk:1.25; 95% CI: 0.77-2.03; I2=37.5%). Although the overall risk of BC was not significantly increased among patients with IBD, the risk was likely to have elevated in CD patients, indicating a marginal significance. These findings may primarily be explained by the opposite effects of smoking on CD and UC, as well as the immunosuppressive drugs applied in them.